THE INFLUENCE OF ADVERTISING EFFECTIVENESS AND BRAND IMAGE OF SAMSUNG GALAXY S4 ON CUSTOMERS PERCEPTION IN MANADO - Makalew, Peggy; Pandowo, Merinda (FEB Universitas Sam Ratulangi Manado, 2015)
The advertising is form of marketing communication used to attract the audience to take some action and it is usually affect by the commercial. The advertising business growing fast and the important thing is how the company communicates the advertising to target market. In this research, the objectives are to investigate the influence of advertising effectiveness and brand image on customers’ perception partially and simultaneously. This research is the causal type of research where it investigates the influence of price, product attributes, origin of product, and philosophy to customer loyalty. Using a multiple regression model to answer the research problem.The populations in this study are people in Manado with the total numbers of sample are 60 respondents. Results and conclusions are advertising effectiveness and brand image influence simultaneously to customers’ perception, then advertising effectiveness has not significant influence on customers’ perception partially, and the brand image has significant influence the customers’ perception partially. This indicate that theSamsung brand advertiser should identify the key attributes and choose those to create the effectiveness of advertisingand know that consumer were very critical about the advertisements and claimed that there were too many advertisements everywhere these days. So the Samsung company advertiser have to put respect on the selection of media and also considering the actual information of an image of a brand. Keywords: advertising effectiveness, brand image, target market